Asymmetric Baeyer–Villiger oxidation: classical and parallel kinetic resolution of 3-substituted cyclohexanones and desymmetrization of meso-disubstituted cycloketones. Issue 29 (17th June 2019) - Wu, Wangbin; Cao, Weidi; Hu, Linfeng; Su, Zhishan; Liu, Xiaohua; Feng, Xiaoming
Abstract : Classical kinetic resolution, parallel kinetic resolution and desymmetrization were achieved by asymmetric BV oxidation of 3-substituted and meso-disubstituted cycloketones. Abstract : Regioselectivity is a crucial issue in Baeyer–Villiger (BV) oxidation. To date, few reports have addressed asymmetric BV oxidation of 3-substituted cycloketones due to the high difficulty of controlling regio- and stereoselectivity. Herein, we report the asymmetric BV oxidation of 3-substituted and meso -disubstituted cycloketones with chiral N, N ′-dioxide/Sc(iii ) catalysts performed in three ways: classical kinetic resolution, parallel kinetic resolution and desymmetrization. The methodology was applied in the total and formal synthesis of bioactive compounds and natural products. Control experiments and calculations demonstrated that flexible and adjustable catalysts played a significant role in the chiral recognition of substrates.